Uma proposta dos recursos metadiscursivos em sequência narrativa produzida por alunos do Povo Pitaguary: um reavivamento da memória - Vidal, Beatriz Barroso Lima (2024)
Preserving an indigenous culture is important and it means the perpetuation of a people’s history. Based on this idea, through the union of the academic universe and the middle school environment, we developed our studies on metadiscourse from the perspective of Hyland (2005), Santos (2011), allied to the conception of referencing by Cavalcante _et al_ (2022), the viewpoint of Rabatel (2016) and the theory of textual sequences proposed by Adam (2019); all these concepts are anchored in Text Linguistics. Our aim is to observe how the Pitaguary indigenous students position and engage themselves, while having their indigenous identity, discursively through their written productions of legends from the local oral culture. The line of approach followed in this work was the action research methodology (Thiollent, 1986), that was applied to an 8th grade class in the final years of middle school, but only the students who took part in all the proposed workshops were taken into account. This way, we collected a _corpus_ of 8 legends, in which we can verify the occurrence of various metadiscursive resources and elements that compose referencing, allowing us to conclude that the legend genre, being mostly composed of narrative sequence, provides the incidence of microcategories of engagement and positioning. In addition, this work gives to Pitaguary community a written compilation of their stories, which often only exist oraly. This is very important, because it strengthens and revives what is considered mystical and sacred in the culture of an indigenous community: the legends that make up their history.